Restoration of Hip Geometry after Femoral Neck Fracture: A Comparison of the Femoral Neck System (FNS) and the Dynamic Hip Screw (DHS) - Marcel Niemann; Tazio Maleitzke; Markus Jahn; Katharina Salmoukas; Karl F. Braun; Frank Graef; Ulrich Stöckle; Sebastian Meller (Life, 2023)
Background: The femoral neck system (FNS) was introduced as a minimally invasive fixation device for managing femoral neck fractures. Objective: To compare radiographic, clinical, and patient-reported outcome measures (PROMs) of femoral neck fracture patients following FNS compared to dynamic hip screw (DHS) implantation combined with an anti-rotational screw. Methods: Patients who underwent closed reduction and internal fixation of a femoral neck fracture between 2020 and 2022 were retrospectively included. We measured leg length, femoral offset, and centrum–collum–diaphyseal (CCD) angle in plain radiographs. Scar length, Harris Hip Score, short-form health survey 36-item score (SF-36), and Numeric Rating Scale (NRS) were assessed during follow-up visits. Results: We included 43 patients (22 females) with a median age of 66 (IQR 57, 75). In both groups, leg length differences between the injured and the contralateral side increased, and femoral offset and CCD angle differences were maintained over time. FNS patients had shorter scars and reported fewer emotional problems and more energy. There were no differences between groups regarding the remaining SF-36 sub-scores, Harris Hip Score, and NRS. Conclusions: The FNS allows for a comparable leg length, femoral offset, and CCD angle reconstruction while achieving similarly high functional and global health scores to the DHS.